A Dirac-Kähler approach to the two dimensional Wess-Zumino N = 2model on the lattice - Aratyn, H.; Zimerman, A. H. (Elsevier, 1984)
We apply the Dirac-Kähler formalism to the two dimensional Wess-Zumino N = 2 model. On the hamiltonian lattice the model exhibits invariance under a lattice subalgebra of supersymmetry. We also describe the euclidean space-time lattice version of this model with the action invariant under the supersymmetry transformations which have the correct continuum limit. © 1984.